Electromagnetic solids with irreversible process of local mass displacement - Kondrat, V.; Hrytsyna, O. (Archives of Mechanics, 2011)
The non-local model of electromagnetothermomechanics for polarized nonferromagnetic solids is proposed. It takes into account the process of local mass displacement due to structural changes of a physically small element of a body. An approach which takes into account possible irreversibility of the local mass displacement is also proposed. On this basis, we have obtained the rheological constitutive relations for the vectors of the mass displacement and for the polarization. The proposed model allows to study the surface charge kinetics and the formation of near-surface inhomogeneities of the stress-strained state as well as the electric polarization, surface tension and disjoining pressure.